Konsep Cyber Notary Dalam Menjamin Keautentikan Terhadap Transaksi Elektronik - Suwantara, I Putu; Pratama Sukma, Putu Angga (Acta Comitas; Vol 6 No 01 (2021)DO - 10.24843/AC.2021.v06.i01.p15, 2021)
The purpose of this paper is to analyze the application form of the concept of cyber notary in guaranteeing the authenticity of electronic transactions and to examine notary arrangements in guaranteeing the authenticity of electronic transactions. This is a departure from the vagueness of norms in Article 15 paragraph (3) of the Law on Notary Position, regarding the need for legal norms on the function and role of notaries in electronic business transactions. This paper uses a normative legal research method because the focus of the study departs from the obscurity of norms. The form of application of the concept of cyber notary in guaranteeing the authenticity of electronic transactions is that the parties keep coming and dealing with the notaries. However, the parties immediately read the draft deed on their respective computers, after agreeing, the parties immediately signed the deed electronically at the notary's office. Notary arrangements in guaranteeing the authenticity of electronic transactions play a role in the issuance of electronic certificates through Electronic Certification Providers. The role of a notary for Certification Authority and in issuing Electronic Certificates through Electronic Certification Providers.   Tujuan penulisan ini adalah untuk menganalisa bentuk penerapan dari konsep cyber notary dalam menjamin keautentikan terhadap transaksi elektronik dan mengkaji pengaturan notaris dalam menjamin keautentikan terhadap transaksi elektronik. Hal tersebut beranjak dari adanya kekaburan norma dalam Pasal 15 ayat (3) Undang Undang Jabatan Notaris, akan kebutuhan norma hukum terhadap fungsi dan peran notaris dalam transaksi bisnis elektronik. Tulisan ini menggunakan metode penelitian hukum normatif karena fokus kajian beranjak dari kekaburan norma. Bentuk penerapan dari konsep cyber notary dalam menjamin keautentikan terhadap transaksi elektronik adalah para pihak tetap datang dan berhadapan dengan para notarisnya. Hanya saja, para pihak langsung membaca draft aktanya di masing-masing komputer, setelah sepakat, para pihak segera menandatangani akta tersebut secara elektronik di kantor Notaris. Pengaturan notaris dalam menjamin keautentikan terhadap transaksi elektronik berperan dalam penerbitan sertifikat elektronik melalui lembaga Penyelenggara Sertifikasi Elektronik. Peran notaris untuk Certification Authority maupun dalam penerbitan Sertifikat Elektronik melalui Penyelenggara Sertifikasi Elektronik .